Peningkatan Kemampuan Pemecahkan Masalah Peserta Didik pada Mata Pelajaran Al Qur’an Hadits melalui Literasi Agama - Anly Maria; Nenden Rieda Dwi Shavitri (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
This research discusses increasing students' abilities in solving problems in Al Qur'an Hadith subjects through a religious literacy approach at MAN 1 Garut. The ability to solve problems is an important skill that students must have in understanding religious teachings and applying them in everyday life. However, in reality, this ability in phase F students is still relatively low. This is proven by the results of observations which show students' achievement in problem solving, namely 33% out of 100% who are able to analyze and solve problems well. Therefore, an effective learning approach is needed, one of which is through religious literacy. Religious literacy is a learning strategy that combines understanding religious texts with critical thinking skills. The aim of this research is to describe the significance of the application of religious literacy in improving problem-solving abilities in the Al-Qur'an Hadith Phase F subject. This research uses a type of Classroom Action Research (CAR) which consists of planning, implementation, observation and reflection stages. Data collection techniques are carried out through observation, ability tests, interviews, and documentation studies. The data analysis technique uses simple quantitative descriptive analysis to calculate the average and percentage increase in students' abilities. Based on the results of research conducted over two cycles, there was an increase in problem solving abilities in the pre-cycle of 38% of a total of 36 students, in the first cycle it was 55.6% and increased again in the second cycle to 88.9%. Thus, it can be concluded that the application of the religious literacy approach has had a significant impact on increasing problem-solving abilities, with an overall increase of 55.9% from pre-cycle to cycle II. Keywords: religious literacy, problem-solving skills, al-qur'an hadith, classroom action research